2001
DOI: 10.1007/s005340170023
|View full text |Cite
|
Sign up to set email alerts
|

Blood supply to the duodenal papilla and the communicating artery between the anterior and posterior pancreaticoduodenal arterial arcades

Abstract: The communicating artery (ComA) between the anterior and posterior pancreaticoduodenal arterial arcades is little understood, although it has been described several times during the past 100 years. In 44 of 51 cadaveric specimens in the present study, the typical ComA was observed to pass between the major and accessory pancreatic ducts. In addition, a second ComA was sometimes found crossing inferior to the major pancreatic duct. The typical ComAs often (36 of the 44) issued papillary branch(es). Although dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The following three factors made frenulum to be vulnerable for bleeding. Firstly, as feeding artery of the lower part of the ampulla including frenulum is tripled supplied with anterior superior pancreaticoduodenal artery, posterior superior pancreaticoduodenal artery, and inferior pancreartic artery . Second is the vulnerable site for delayed bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The following three factors made frenulum to be vulnerable for bleeding. Firstly, as feeding artery of the lower part of the ampulla including frenulum is tripled supplied with anterior superior pancreaticoduodenal artery, posterior superior pancreaticoduodenal artery, and inferior pancreartic artery . Second is the vulnerable site for delayed bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Falconer and Griffiths () found it in 11 cases of a series composed of 27 dissections and 23 corrosion casts. This anastomotic arcade occurred in 20% of our series, while Yamaguchi et al () found it surprisingly as an almost constant vascular variation (86%) in 51 examined Japanese samples.…”
Section: Discussionmentioning
confidence: 99%
“…This type of embolic agent penetrates deeply into the targeted tissues and blocks the arterial circulation at the level of arterioles with a diameter of 300-500 micron. The rich collateral arterial network in the upper abdomen, with many anastomoses, particularly between the anterior and posterior pancreaticoduodenal arcades, may explain the absence of ischaemic complications after aggressive embolotherapy [15].…”
Section: Discussionmentioning
confidence: 99%